PENGARUH PENAMBAHAN SORBITOL TERHADAP KARAKTERISTIK FISIKOKIMIA EDIBLE FILM BERBAHAN DASAR PATI GANDUM - Riyanto, Diva Nathania; Utomo, Adrianus Rulianto; Setijawati, Erni (Widya Mandala Surabaya Catholic University, 2017)
The usage of plastics as food packaging is very widely used in Indonesia. Plastic is a packing material which still dominates because as a good barrier properties against oxygen, carbon dioxide and water vapor. The weakness of this plastic is its non biodegradable characteristic so to overcome this problem, an alternate packaging material is developed by making the packaging biodegradable and edible. Wheat starch granule has a lipid amount of 0,7 to 1,4%, wheat starch has amylose content quite high at 25%. The existence of lipid which will tend to complex with the amylose of the starch and reduce its water-binding capacity. This study aimed to determine the effects of sorbitol on the physicochemical characteristics of the edible film. This study uses a mathematical data analysis regression which consists of a single factor, the addition of sorbitol concentration factor with seven levels of treatment: 1%; 1,2%; 1,4%; 1,6%; 1.8%; 2%; 2,2% (w/w). Edible film has water content 5.7 - 11.46% ; percent elongation 2,56 - 11,94% ; percent of dissolution 39,14 – 64,04% ; water vapor permeability 5,49 x 10-9 – 1,67 x 10-9 g/m.h.Pa, and tensile strength 132,04 – 339,15 kg/cm2.